2023
DOI: 10.1002/advs.202300953
|View full text |Cite
|
Sign up to set email alerts
|

Smoking‐Induced M2‐TAMs, via circEML4 in EVs, Promote the Progression of NSCLC through ALKBH5‐Regulated m6A Modification of SOCS2 in NSCLC Cells

Abstract: Lung cancer is a commonly diagnosed disease worldwide, with non-small cell lung cancers (NSCLCs) accounting for ≈ 85% of cases. Cigarette smoke is an environmental exposure promoting progression of NSCLC, but its role is poorly understood. This study reports that smoking-induced accumulation of M2-type tumor-associated macrophages (M2-TAMs) surrounding NSCLC tissues promotes malignancy. Specifically, extracellular vesicles (EVs) from cigarette smoke extract (CSE)-induced M2 macrophages promoted malignancy of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Smoking status is also considered a potential risk factor for disease progression. Cheng et al (40)found that smoking has the potential to accelerate tumor progression, a phenomenon attributed to the smoking-induced accumulation of M2-tumor-associated macrophages (M2-TAMs) around non-small cell lung cancer tissue. In addition, radiation therapy is considered to be one of the most effective methods of tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking status is also considered a potential risk factor for disease progression. Cheng et al (40)found that smoking has the potential to accelerate tumor progression, a phenomenon attributed to the smoking-induced accumulation of M2-tumor-associated macrophages (M2-TAMs) around non-small cell lung cancer tissue. In addition, radiation therapy is considered to be one of the most effective methods of tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…Lower circCIMT expression was associated with DNA damage in the mouse lung tissue and blood after Cd exposure, which contributing to the acquisition of tumor characteristics of lung epithelial cells ( Li et al, 2023 ). What’s more, smoking-induced M2 macrophages via circEML4 in extracellular vesicles promote the non small cell lung cancer progression through ALKBH5-regulated m6A modification of SOCS2, which leading to the activation of JAK-STAT pathway ( Cheng et al, 2023 ). Similarly, CircTMEM30A was highly expressed in COPD patients with lung cancer, and it regulated the expression of TNFα through miR-130a, thereby promoting the progression of COPD and lung cancer ( Shen et al, 2023 ).…”
Section: Circrnas In Inhalation Lung Injurymentioning
confidence: 99%
“…Besides its involvement in various physiological and autoimmune diseases, circRNA also plays an important role in the onset and progression of various malignant tumors ( 54 ), cell proliferation ( 55 ), cell apoptosis, and metastasis ( 56 ). With advancements in bioinformatics technology, an increasing number of circRNAs have been shown to play different biological functions in various cancer systems via multiple pathways ( 57 , 58 ).…”
Section: Roles and Mechanisms Of Circrna In Respiratory Cancersmentioning
confidence: 99%